ANALISIS KEBUTUHAN BAHAN AJAR MATA KULIAH BIOLOGI DASAR - GH, Muliana; Irfan, M (BIOMA: Jurnal Biologi dan Pembelajarannya, 2024)
This research aims to determine the learning materials needs of students in the basic biology course. The research method employed is qualitative descriptive method. The research instrument utilizes a digital-based needs analysis questionnaire (Google Forms platform). The respondents in this study are 55 students from Makassar State University who have taken the basic biology course. Data collection is conducted by distributing a needs analysis questionnaire for the basic biology course learning materials. The findings of this research indicate that the basic biology material is perceived as difficult due to its complexity and abundance. Common challenges faced by students in learning include instructional media, where students commonly rely on freely available internet sources for learning materials. Specifically, topics such as inheritance of traits and genetics are considered difficult by students, while topics related to the structure and function of animals are perceived as easier. The results of this study are expected to serve as a basis for the development of learning materials or resources for the basic biology course that align with the characteristics of the learners. Keywords— Analysis, Teaching Materials, Basic Biology Course